A magic formula for economic development? Global market integration and spatial polarization in extractive industries. Issue 3 (3rd July 2021) - Scholvin, Sören; Breul, Moritz; Diez, Javier Revilla
ABSTRACT: The World Bank, World Trade Organization and others promote integration into global markets as a certain path towards economic development. Some researchers share this optimism, arguing that development is the record of how one thing leads to another, once peripheral locations have plugged into global networks. Comparing resource peripheries in South America, Southeast Asia and Sub-Saharan Africa with regard to the upstream oil and gas sector, we call for a more nuanced assessment. Against the backdrop of 38 narrative, open-ended interviews, we show that there is spatial polarization between 'gateways' and peripheral sites in Southeast Asia. Argentinean and Ghanaian case studies reveal that local firms usually provide generic services, with little prospects of venturing into higher value-adding activities. We conclude that at least the oil and gas sector is not suitable for fulfilling very optimistic expectations on development.